2023
DOI: 10.3389/fpsyg.2023.1236070
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional intelligence, anxiety, and performance in physical education and sport students

Wael Zoghlami,
Aymen Hawani,
Hyem Khiari
et al.

Abstract: Emotional intelligence (EI) has been recently the main target in research on sports psychology. The objectives of this study were to investigate the relation between self-report measures of emotional intelligence, pre-competitive anxiety, and performance among students during the physical education exam of the high school final year. This cross-sectional study was conducted on a sample of 350 students attending the physical education exam in the year 2021–2022. Analysis of the correlations between the scores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…• promote e-learning programs and information systems on the Internet. In this regard, as noted by W. Zoghlami et al, when training specialists in the field of physical culture and sports in higher education, special attention must be paid not only to the transfer of professionally oriented knowledge, but to the formation of skills in the educational process, the development of professionally significant personality qualities, abilities for independent creative, innovative work, including in a foreign language and using digital technologies [12]. K. S. Popenko, A. S. Makhov note that knowledge of foreign languages, especially English as a language of international communication, is a necessary condition for successful professional activity [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…• promote e-learning programs and information systems on the Internet. In this regard, as noted by W. Zoghlami et al, when training specialists in the field of physical culture and sports in higher education, special attention must be paid not only to the transfer of professionally oriented knowledge, but to the formation of skills in the educational process, the development of professionally significant personality qualities, abilities for independent creative, innovative work, including in a foreign language and using digital technologies [12]. K. S. Popenko, A. S. Makhov note that knowledge of foreign languages, especially English as a language of international communication, is a necessary condition for successful professional activity [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…self-concept (71,72,73). Furthermore, there are many commonalities that can be found between PE and other subjects that can provide ideas for integrating them:…”
Section: Interactions With Other Subjectsmentioning
confidence: 99%
“…Some studies showed that intrinsic motivation, satisfaction, and physical enjoyment improved physical performance [ 30 , 31 ]. Physical enjoyment can also be described as an affective and emotional reaction to a physical education session that could generate a certain satisfaction, pleasure self-confidence, and more satisfactory emotion management during physical education and sport, in children and adolescents with and without disability [ [25] , [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%